Multi-wavelength Brillouin fiber laser using Brillouin-Rayleigh scatterings in distributed Raman amplifier - Shahi, Sharifeh; Harun, Sulaiman Wadi; Ahmad, Harith (IOP Publishing, 2009)
An efficient multi-wavelength Brillouin fiber laser (BFL) is demonstrated by using a self feedback mechanism of Brillouin-Rayleigh scatterings with the presence of distributed Raman gain. The balanced of these three scatterings generates a laser comb more than 27 lines with a relatively flat amplitude and constant spacing of 0.09 nm. This is realised using a piece of dispersion compensating fiber as the nonlinear gain medium, an amplified Brillouin pump and a broad-band fiber Bragg grating as a reflector.